Специфіка професійного мислення робітників гірничого профілю - Тарасова, О. В. (НТУ "ХПІ", 2009)
Mining workers professional activity is discussed in the article, the author also makes structural job analysis which sinker, carman and excavator driver make. Individual psychological features and specific character of mining workers professional thinking are characterized in the article. Psychological and pedagogical conditions of mining vocational schools students professional thinking development are proved in the article
Keywords: професійно-технічне навчання; професії гірничого профілю; професія прохідника; професійне мислення